2021
DOI: 10.14797/mdcvj.699
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Proptosis (Exophthalmos) Caused by Axillary-Subclavian Venous Thrombosis in a Patient with Upper Extremity Arteriovenous Dialysis Fistula

Abstract: Arterialization of orbital veins is most often due to dural arteriovenous malformations of the cavernous sinus area. We report an unusual case of unilateral proptosis (exophthalmos) caused by arterialized retrograde venous flow in the external jugular vein and cavernous sinus in a patient with an upper extremity hemodialysis fistula and ipsilateral acute central venous thrombosis. The patient’s symptoms improved after surgical closure of the hemodialysis fistula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…2,5–11 Notably, as seen in our patient, all of these patients had improvement in symptoms following intervention with ligation of the fistula or balloon dilation of the stenotic brachiocephalic vein. 2 Gómez-Arbeláez et al 12 identified 3 cases of proptosis in this patient group, 1 of which was bilateral as seen in our patient. 13–14 SOV dilation also has been infrequently described in this patient group but is generally unilateral.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…2,5–11 Notably, as seen in our patient, all of these patients had improvement in symptoms following intervention with ligation of the fistula or balloon dilation of the stenotic brachiocephalic vein. 2 Gómez-Arbeláez et al 12 identified 3 cases of proptosis in this patient group, 1 of which was bilateral as seen in our patient. 13–14 SOV dilation also has been infrequently described in this patient group but is generally unilateral.…”
Section: Discussionsupporting
confidence: 65%
“…2,5–8,13 Interestingly, all but one of the previously reported patients with ocular findings due to arteriovenous peripheral access had optic disc swelling. 4–8,12–17 Our patient did not have optic disc swelling at presentation, but he had a subtle left relative afferent pupillary defect indicating a mild left optic neuropathy, and he endorsed tinnitus, which might have indicated increased intracranial pressure. However, the overall prevalence of optic disc swelling in asymptomatic patients with arteriovenous dialysis access is unknown but is likely low.…”
Section: Discussionmentioning
confidence: 74%